DAMPAK PANDEMI COVID-19 TERHADAP PEMANFAATAN PELAYANAN KESEHATAN PASIEN RAWAT INAP DI RSU THALIA IRHAM - Erni Kadir (Asosiasi Dosen Muda Indonesia, 2022)
Utilization of health services can be influenced by factors such as facilities, time, distance, cost, price, the smoothness of the doctor-patient relationship, quality of service, community psychology and the community's own concept of illness. The purpose of this study was to find out in-depth information about the Impact of the Covid 19 Pandemic Regarding the Utilization of Health Services for Inpatients at Thalia Irham Hospital, Bajeng District, Gowa Regency in 2021. This research method is a qualitative study with a total of 6 informants. The results of this study are that basically all the informants know about the COVID-19 pandemic, how to prevent it, the application of health protocols, policies during the pandami period and the countermeasures that make people want to take advantage of health services at the Thalia Irham Gowa hospital. There was a change in policy during the Covid 19 pandemic at the Thalia Irham Hospital where some people rejected this policy which made people less use of health services. The occurrence of the Covid 19 pandemic requires a change in behavior in the community towards the use of health services, there is psychological pressure experienced by the community if they have their health checked such as being afraid of being sentenced to corona, although there are some people who do not believe in the existence of corona disease but are also lacking in utilizing health services. The suggestion from this research is that it is suggested to the management of the hospital to increase the knowledge of visitors/patients by providing an understanding through counseling about corona disease every time a doctor visits a patient. There needs to be a flow/stage of health services during the Covid 19 pandemic that is clearly visible and easily understood by patients. It is recommended that the Thalia Irham Gowa Hospital take part in outreach to the community around the hospital about the negative issues of corona disease so that people are not afraid to go to the health service to check their health.